Contamination status and toxicity risk assessment of selected potentially toxic elements in surface soils under the influence of different land uses in Midwestern Burkina Faso, West Africa - Michel Bembamba; Aboubakar Sako (Journal of Trace Elements and Minerals)
Background: As land use transitions from rain-fed farming to market gardening and artisanal gold mining in Burkina Faso, soil contamination with potentially toxic elements (PTEs) has become a major environmental concern. Objective: This study investigates the PTE pollution status of highly anthropized soil in Midwestern Burkina Faso. Methods: A total of 226 topsoil samples were collected, and their PTE concentrations were determined using inductively coupled plasma mass spectrometry (ICP-MS). Enrichment factors and ecological and toxicity risk indices were used to evaluate the soil's contamination status. Results: The results revealed that artisanal gold mining mainly contributed to Ag, As, Cd, Cu, Ni, and Zn loadings in the soils, whereas agricultural practices might have partially contributed to Pb concentrations. Based on the spatial distribution maps of the ecological risk index (RI), the studied soils exhibited low (23–104), moderate (150 ≤ RI < 300), and very high (RI>600) risk levels. Samples with high toxicity units (ΣTU > 4) and toxicity risk index (TRI > 20) were clustered around artisanal gold mining sites. The strong spatial and linear correlations between ΣTU and RI (r² = 0.79), and between RI and TRI (r² = 0.90), suggest that the newly developed toxicity indices are suitable for assessing PTE toxicity in soils. Conclusion: The study's findings demonstrate that, in addition to chemical weathering, uncontrolled artisanal gold mining activities and, to a lesser degree, agricultural practices are likely to threaten soil functioning and food security. The study provides valuable insights into the ongoing global discourse on PTE distribution and its effects on soil environmental quality.